Application of a PBPK model to elucidate the changes of systemic and liver exposures for rosuvastatin, carotegrast, and bromfenac followed by OATP inhibition in monkeys. Issue 5 (31st May 2021) - Cheng, Yaofeng; Liang, Xiaomin; Hao, Jia; Niu, Congrong; Lai, Yurong
Abstract: The impact of organic anion‐transporting polypeptide (OATP) inhibition on systemic and liver exposures of three OATP substrates was investigated in cynomolgus monkeys. A monkey physiologically‐based pharmacokinetic (PBPK) model was constructed to describe the exposure changes followed by OATP functional attenuation. Rosuvastatin, bromfenac, and carotegrast were administered as a single intravenous cassette dose (0.5 mg/kg each) in monkeys with and without predosing with rifampin (RIF; 20 mg/kg) orally. The plasma exposure of rosuvastatin, bromfenac, carotegrast, and OATP biomarkers, coproporphyrin I (CP‐I) and CP‐III were increased 2.3, 2.1, 9.1, 5.4, and 8.8‐fold, respectively, when compared to the vehicle group. The liver to plasma ratios of rosuvastatin and bromfenac were reduced but the liver concentration of the drugs remained unchanged by RIF treatment. The liver concentrations of carotegrast, CP‐I, and CP‐III were unchanged at 1 h but increased at 6 h in the RIF‐treated group. The passive permeability, active uptake, and biliary excretion were characterized in suspended and sandwich‐cultured monkey hepatocytes and then incorporated into the monkey PBPK model. As demonstrated by the PBPK model, the plasma exposure is increased through OATP inhibition while liver exposure is maintained by passive permeability driven from an elevated plasma level. Liver exposure is sensitive to the changes of metabolism and biliary clearances. The model further suggested the involvement of additional mechanisms for hepatic uptakes of rosuvastatin and bromfenac, and of the inhibition of biliary excretion for carotegrast, CP‐I, and CP‐III by RIF. Collectively, impaired OATP function would not reduce the liver exposure of its substrates in monkeys.